Cell Cycle– and Chaperone-Mediated Regulation of H3K56ac Incorporation in Yeast - Kaplan, Tommy (Public Library of Science, 2008)
Acetylation of histone H3 lysine 56 is a covalent modification best known as a mark of newly replicated chromatin, but it has also been linked to replication-independent histone replacement. Here, we measured H3K56ac levels at single-nucleosome resolution in asynchronously growing yeast cultures, as well as in yeast proceeding synchronously through the cell cycle. We developed a quantitative model of H3K56ac kinetics, which shows that H3K56ac is largely explained by the genomic replication timing and the turnover rate of each nucleosome, suggesting that cell cycle profiles of H3K56ac should reveal most first-time nucleosome incorporation events. However, since the deacetylases Hst3/4 prevent use of H3K56ac as a marker for histone deposition during M phase, we also directly measured M phase histone replacement rates. We report a global decrease in turnover rates during M phase and a further specific decrease in turnover at several early origins of replication, which switch from rapidly replaced in G1 phase to stably bound during M phase. Finally, by measuring H3 replacement in yeast deleted for the H3K56 acetyltransferase Rtt109 and its two co-chaperones Asf1 and Vps75, we find evidence that Rtt109 and Asf1 preferentially enhance histone replacement at rapidly replaced nucleosomes, whereas Vps75 appears to inhibit histone turnover at those loci. These results provide a broad perspective on histone replacement/incorporation throughout the cell cycle and suggest that H3K56 acetylation provides a positive-feedback loop by which replacement of a nucleosome enhances subsequent replacement at the same location.